Primary Intracranial Extraskeletal Mesenchymal Chondrosarcoma of the Brain in a Pediatric Patient: A Case Report and Review of Literature - Debanjan Sikdar; Sweety Gupta; Ravi Roshan; Shruti Agarwal; Deepa M. Joseph; Manoj Gupta (Indian Journal of Medical and Paediatric Oncology)
Intracranial extraskeletal mesenchymal chondrosarcoma, which is characterized by undifferentiated mesenchymal cells in the presence of occasional pockets of mature hyaline cartilage, is rare in our clinical practice and commonly seen in young adults. In the pediatric population, only a few cases have been reported. In this article, we describe a case of primary recurrent intracranial mesenchymal chondrosarcoma in an 11-year-old boy well treated by surgery, radiation, and chemotherapy. We also reviewed all previously published reports on pediatric patients on the basis of their manifestations and management.